UPAYA PELESTARIAN MACAPAT DALAM RITUAL CUKUR RAMBUT GEMBEL DI DESA DIENG KULON, KABUPATEN BANJARNEGARAPenelitian ini bertujuan untuk mengetahui upaya pelestarian macapat yang terdapat pada ritual cukur rambut gembel di Desa Dieng Kulon, Banjarnegara. Pe (Catharsis, 2022)
This study aims to determine the efforts to preserve macapat songs in the shaving ritual of dreadlock hair in Dieng Kulon Village, Banjarnegara. This study used a qualitative method with an interdisciplinary approach, including the disciplines of anthropology and sociology. The data collection techniques used observation, interviews, and document studies, while the research validation used the criteria for the degree of trust (credibility) with data triangulation techniques. The analysis of this research was carried out in the order of problem selection, initial observation, data reduction, and final research result. The study results indicate that a strong motivation from the community that owns the culture is needed for implementing cultural preservation. The preservation of macapat in Dieng Kulon Village works because of the consistency of the community in applying it in their daily life. In addition, the local government supports the implementation of the event, the teaching educational institutions use the songs, and the presence of macapat at the Dieng Culture Festival event was formed by community organizations.